Differences in consumer decision-making styles among selected South-east European countries - Anić, I-D; Ciunova shuleska, Anita; Piri Rajh, S; Edo Rajh; Bevanda A. (Economic Research, 2016)
Fast changes in retailing and complex consumer decision-making processes have increased the need for additional investigation of differences and similarities in consumer decision-making styles (CDMS) in various countries. This paper tests the reliability and validity of Sproles and Kendall’s Consumer Style Inventory (CSI) instrument, identifies and compares CDMS in Croatia, Bosnia and Herzegovina and Macedonia (FYR). Data obtained from surveys conducted among university students in observed countries (n = 1.206) were analysed by using exploratory and confirmatory factor analyses and the analysis of variance (ANOVA). The results provided support for six factors, which means that the original US eight-model cannot be fully applied in this region. Croatian consumers are the least brand-conscious and novelty-fashion conscious. Macedonian consumers are the most quality-conscious, brand-conscious, novelty-fashion conscious, recreational shopping conscious and brand-loyal, while Bosnian consumers are the most confused by overchoice. The traits of price consciousness and impulsiveness were not tested because of lack of reliability among items. The paper provides guidelines for marketers on how to position and more effectively advertise their products and services in analysed countries.
Keywords: Consumer decision-making styles; CSI instrument; crosscultural differences; southeast European countries